Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Pengolahan Buah Pisang Menjadi Cookies di Kelurahan Wawonggole Kabupaten Konawe - Leni Saleh; Endang Sumiratin; Mursal Junus; Aryana Aryana; Sebriani Sebriani; Sinta Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of holding this PKM activity is to make processed bananas into Banana Sticks and Banana Chocolatos for the women of RT 001 Wawonggole Village, Unaaha District. The selected participants were 15 people. The community service activities carried out in Wawonggole Village for the women of RT 001 went well, the participants were enthusiastic in taking part in the training activities. Through this training activity, the women of RT 001 came to understand and be able to make processed agricultural products, especially bananas, into Banana Sticks and Banana Chocolatos, the ingredients of which are easy to obtain and the manufacturing process is easy. Community service activities in Wawonggole Village received a positive response, of course this can be followed up at a later time